Macrosegregation modeling during direct-chill casting of aluminum alloy 7050. (1st November 2016) - Fezi, Kyle; Plotkowski, Alex; Krane, Matthew John M.
ABSTRACT: A fully transient model of the direct-chill casting process is used to predict the macrosegregation development of aluminum alloy 7050. The ingot diameter, casting speed, superheat, secondary cooling, and thickness of pure Al at startup are varied. Predicted radial composition distributions are fit to Weibull probability density functions at each axial location, and the normalized standard deviation describes the macrosegregation level and the time when the process reaches steady state. The sump depth, steady-state height, and macrosegregation level were most affected by changes in casting speed and ingot diameter. The pure Al dilutes the alloy and delays compositional steady state.